Naming and forgetting: Sowa Rigpa and the territory of Asian medical systems (Medicine Anthropology Theory, 2016)
Sowa Rigpa is generally translated as ‘the science of healing’ and often used synonymously for ‘Tibetan medicine’. Historically, Sowa Rigpa can be considered a borrowed term from Sanskrit, accompanied by an adopted sense of ‘science’, which initially signified all forms of medicine known to the Tibetan world, regardless of their place of origin. Over the centuries, Sowa Rigpa became linked to local, indigenous, and ‘enskilled’ practices; later, to nationalist political sensibilities; and of late to cultural belonging. The term evokes territoriality, claims to ownership of knowledge, concerns over sustaining national identities, and considerations about how place-based healing practices and material resources relate to the globalizing ideas about traditional Asian medicines. Textual and ethnographic analyses and interviews with practitioners from China, India, and Nepal show how Sowa Rigpa exists at once as a marker of shared intellectual and cultural histories and forms of medical practice and as a label for a globally circulating medical system with distinct interpretations. Looking at Sowa Rigpa as operating in de- and reterritorialized global spaces makes visible how, why, and to what end modernity forgets (Connerton 2009), thereby allowing for broader conclusions applicable to other medical contexts.